Profitability Analysis Of Bean Engineering On UD. Ranggina Bean Two Brothers In Lalona Village, Bungku Central District Morowali Regency - Alma Gebriani; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This study aims to analyze the profitability of the peanut rengginang business in the Two Brothers Home Industry in Lalona Village, Bungku Tengah District, Morowali Regency. Determination of the research location purposively. Data was collected using a questionnaire, interview, and documentation methods—research analysis using profitability ratios. The results of the study show that the analysis of profitability in the home industry of the two brothers in 2020 shows that the profitability ratio for the net profit margin (NPM), which is 55.42% is above the average or very good. The profitability ratio of the return on assets (ROA) value is equal to 132% are, above average or very good. Based on the calculation of net profit margin (NPM) and return on assets (ROA), Home Industry is very efficient and profitable to run.